Alterations in carotenoids, phenolic compounds, flavonoids and ascorbic acid contents in red mombin (Spondias purpurea L.) microencapsulated pulp - Todisco, Katieli Martins [UNESP]; da Costa, José Maria Correia; Clemente, Edmar (My University, 2015)
Red mombin is a species that is native to Central America, but is also found in several areas of Brazil. Fruit consumption has increased due to their nutritional and therapeutic effects. This sort of food contains different phytochemical compounds, including compounds with antioxidant properties. The demand for native and exotic products is growing, especially when it comes to foodstuff, and it creates a need for better comprehension of their processing and properties. This work aimed at studying the storage of red mombin pulp that was dehydrated by atomization and stored in polyethylene and laminated packages during 120 days at 25±2°C and 85±5% of relative humidity. The powder of red mombin was obtained by spray-drying a solution containing 90% of red mombin integral pulp and 10% of maltodextrin at a drying temperature of 120°C. Every 15 days ascorbic acid, total phenolic compounds, yellow flavonoids and total carotenoids were analyzed. For total carotenoids and ascorbic acid, there was a significant difference among the integral pulp samples before the processing and after the atomization. Regarding total phenolic compounds and yellow flavonoids, there was a significant increase in the values after atomization. The results showed that there were alterations in total phenolic compounds and yellow flavonoids. It is possible to observe an oscillation among the different periods of storage in both packages studied. Both packages showed significant oscillations for ascorbic acid, which is one of the most sensitive vitamins, when it comes to heat, and it can be completely destroyed during drying processes. In the content of total carotenoids in both packages, the behaviour was similar in almost all periods of stability.
Keywords: Bioactive compounds; Conservation; Maltodextrin; Packages; Red mombin pulp; Spray-drying